Study of immunoglobulins in pleura and pleural effusions. Issue 3 (June 1979) - Telvi, L; Jaubert, F; Eyquem, A; Andreux, J P; Labrousse, F; Chrétien, J
Abstract : The protein concentration of 35 pleural effusions was compared with that in the serum. The ratio of the pleural and serum concentration of albumin, IgG, IgA, and IgM is always below unity and appears to have no diagnostic value. However, the ratio of the concentration of these proteins was inversely related to their molecular weight. The underlying mechanism in malignant and inflammatory effusions appear similar and is in keeping with a diffusion process. Immunofluorescent staining of the pleura suggests the intercellular passage of the proteins through the mesothelial barrier.